2020
DOI: 10.1111/btp.12771
|View full text |Cite
|
Sign up to set email alerts
|

A historical and comparative review of 50 years of root data collection in Puerto Rico

Abstract: Fine roots play an important role in plant nutrition, as well as in carbon, water, and nutrient cycling. Fine roots account for a third of terrestrial net primary production (NPP), and inclusion of their structure and function in global carbon models should improve predictions of ecosystem responses to climate change. However, studies focusing on underground plant components are much less frequent than those on aboveground structure. This is more marked in the tropics, where one-third of the planet's terrestri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 92 publications
3
13
0
Order By: Relevance
“…In our case, fine‐root biomass was concentrated in the top 20 cm, consistent with available P concentrations gradients (Lynch & Brown, 2001). Similarly, over 80% of root biomass was within the top 20 cm of the soil profile in a comprehensive review of roots in Puerto Rico (Yaffar & Norby, 2020). Global estimates using β to describe root depth distribution indicate that in tropical evergreen forests, where 70% of root biomass is in the upper 30 cm of the soil profile, β = 0.962 (Jackson et al., 1997).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our case, fine‐root biomass was concentrated in the top 20 cm, consistent with available P concentrations gradients (Lynch & Brown, 2001). Similarly, over 80% of root biomass was within the top 20 cm of the soil profile in a comprehensive review of roots in Puerto Rico (Yaffar & Norby, 2020). Global estimates using β to describe root depth distribution indicate that in tropical evergreen forests, where 70% of root biomass is in the upper 30 cm of the soil profile, β = 0.962 (Jackson et al., 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Plant P acquisition within highly weathered tropical soils is determined in part by root expansion throughout the soil volume to capture available P and root physiological mechanisms that alter the soil environment to enhance P availability at the root surface where uptake occurs (Lambers et al., 2006). Prior work within the LEF shows that high fine‐root biomass is concentrated in the first few centimeters of mineral soil (Silver & Vogt, 1993; Yaffar & Norby, 2020), which could enable plants to capture nutrients renewed through litterfall (Silver et al., 1994). Global analysis also indicates that across forest types, 50 % of all roots are within the top 30 cm (Schenk & Jackson, 2002), perhaps due to the shallow distribution of bioavailable P in soil depth profiles (Jobbágy & Jackson, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, hierarchical partitioning revealed that deeper soil moisture, even more so than vegetation temperature or shallow soil moisture, was the most influential climate variable determining variation in many gas exchange parameters (Supplementary Figure S11). Deeper, rather than shallow, soil moisture may have been a stronger driver because it was less variable in general ( Figure 2D; Kimball et al, 2018) likely because of less surface evaporation and fewer roots present to rapidly draw water from that soil depth (Yaffar and Norby, 2020). T opt increased as soil moisture decreased (Figures 8A,B), suggesting that neither species' T opt will likely be negatively affected by a drying climate.…”
Section: Soil Moisture: a Stronger Driver Than Temperaturementioning
confidence: 99%